ChemInform Abstract: Exploiting Distal Reactivity of Coumarins: A Rhodium‐Catalyzed Vinylogous Asymmetric Ring‐Opening Reaction. Issue 31 (14th July 2016) - Loh, Charles C. J.; Schmid, Matthias; Peters, Brendan; Fang, Xiang; Lautens, Mark
Abstract: An unprecedented example of vinylogous reactivity exemplified by the rhodium‐catalyzed asymmetric ring‐opening reaction of oxabicycles leading to the incorporation of the biologically useful coumarin motif into the hydronaphthalene scaffold is presented.